Sosialisasi Konseling Baayun Bagi Konselor Kesehatan di Puskesmas Kesarangan Kabupaten Hulu Sungai Tengah - Sanjaya Sanjaya; Rudi Haryadi; Nurmiati Nurmiati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The Baayun Counseling Socialization Program at the Health Center is designed to improve the understanding and skills of health workers in implementing a more humane and local culture-based counseling approach. Baayun counseling is a therapeutic communication method that integrates cultural values in the interaction between health workers and patients, so that services become more personalized, empathetic, and meaningful. This program is carried out through several stages, namely needs analysis, socialization, and effectiveness evaluation. The main target is health workers in primary services who interact directly with patients. The expected results of this program include improving the competence of health workers in understanding and implementing Baayun Counseling, as well as increasing patient satisfaction and compliance with health services. Program evaluations show that this approach is able to create positive changes in communication patterns, strengthen the relationship between health workers and patients, and improve the overall quality of counseling services. By adopting Baayun Counseling, Puskesmas can strengthen the cultural dimension in health services, making them more relevant and responsive to the needs of local communities. The program also has the potential to be replicated in other culturally rich regions as part of a community-based health service quality improvement strategy.